Do foreign entrepreneurs benefit their firms as managers? - Kulchina, Elena (Strategic Management Journal, 2017)
Research summary: T he entrepreneurship literature has extensively studied an individual's decision to found a new venture, but it has little to say about the individual's choice to operate this venture personally or hire an agent. This decision is particularly challenging for foreign entrepreneurs, who, in addition to traditional factors, such as agency costs and personal preferences, need to take into consideration the benefits and liabilities of foreignness. Using novel data on foreign entrepreneurial firms and instrumenting for the owner‐manager choice with a visa policy change, we find that managing foreign entrepreneurs significantly improve firm performance. Our results further suggest that foreign owner‐managers reduce operating costs but have no effect on the firm's productivity and growth . Managerial summary: I mmigrants represent a significant part of the population in the United States and E urope and are often more entrepreneurial than local nationals. However, a person starting a firm in a foreign country faces unique challenges. One important choice that a foreign entrepreneur has to make is whether to operate the firm personally or hire a local agent. Foreign entrepreneurs are often believed to be worse managers because they have limited local knowledge and skills. However, our results point to the contrary: We find that managing foreign entrepreneurs significantly improve firm performance by decreasing firms' operating costs. This happens because foreign owner‐managers often have access to unique resources, higher work incentives, and superior management skills acquired at home . Copyright © 2016 John Wiley & Sons, Ltd.